(untitled) (Raparin Journal of Humanities (RJH), 2024)
This research aims at revealing the impact of flipped classroom strategy on a number of kinematic variables in the art of performance and achievement of some basic skills in volleyball; recognizing the differences between pre-tests and post-tests for both experimental and control groups، detecting the differences between both experimental and control groups in post hoc tests of the researched variables. Furthermore، the researchers applied the experimental curriculum in order to adapt it to the nature of the research. The research community consists of (160) students (males and females) from the Faculty of Physical Education، and the research sample reached (40) students of the second stage. The sample was then divided into experimental and control groups، randomly putting 20 students in each group; and the tested sample consists of (12) students due to the lack of commitment of some of them to apply the curriculum and the absence of many others. The two researchers then conducted the processes of homogenization and parity of the two groups، all of which show a value greater than 0.05. In addition، the sample ratio reached15%، and the two researchers in this study arrived at the conclusion that there was a difference in measuring skillful performance between accurate measurements (tests) and the measurement of art of performance by the residents. Moreover، the strategy of flipped classroom has the effect of improving some of the kinematic variables (working angles) of some of the basic skills in volleyball. Besides، there are kinematic variables of the human body that have much to do with the stage of learning skills (handling، receiving transmissions)، compared to variables that have little to do with the learning process when emphasized by the instructor.